2022
DOI: 10.5935/0103-507x.20210037-en
|View full text |Cite
|
Sign up to set email alerts
|

What changed between the peak and plateau periods of the first COVID-19 pandemic wave? A multicentric Portuguese cohort study in intensive care

Abstract: Objective To analyze and compare COVID-19 patient characteristics, clinical management and outcomes between the peak and plateau periods of the first pandemic wave in Portugal. Methods This was a multicentric ambispective cohort study including consecutive severe COVID-19 patients between March and August 2020 from 16 Portuguese intensive care units. The peak and plateau periods, respectively, weeks 10 - 16 and 17 - 34, were defined. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Similarly, in our study, previous heart failure increased early mortality and previous severe CKD, COPD and cancer, increased late mortality. Our findings are aligned with prior studies, indicating that the presence of pre-existing comorbidities has a greater impact on post-discharge mortality than the severity of COVID-19 pneumonia itself [ 3 , 15 , 27 , 28 ]. Other cohort studies also showed that previous hypertension and CKD increased both early and late mortality [ 29 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in our study, previous heart failure increased early mortality and previous severe CKD, COPD and cancer, increased late mortality. Our findings are aligned with prior studies, indicating that the presence of pre-existing comorbidities has a greater impact on post-discharge mortality than the severity of COVID-19 pneumonia itself [ 3 , 15 , 27 , 28 ]. Other cohort studies also showed that previous hypertension and CKD increased both early and late mortality [ 29 31 ].…”
Section: Discussionsupporting
confidence: 91%